The Role of The Gender of Directors, Proportion of Independent Board of Commissioners, and Public Ownership on Corporate Social Responsibility Disclosure of Banks In Indonesia - Nadania Yuniar; Shafa Fadia Zainavy; Tiara Meilan Putri; Ainunnisa Al Rumra (Universitas Muhammadiyah Purwokerto, 2023)
This purpose of this study was to determine the effect of Gender of Directors, Proportion of Independent Commissioners, and Public Ownership on the Disclosure of Corporate Social Responsibility. The population used in this study are banking companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The sampling technique used was purposive sampling and 119 samples were obtained that met the criteria. The analytical method used is multiple regression. The results of this study showed that the Gender of Directors has a positive effect on CSR, while the Proportion of Independent Commissioners and Public Ownership has no effect on CSR disclosure.